Letter (copy) : Grant - Citrine, Walter, 1887-1983
041-0066-001 WMC/HVT/FC/478. Secretary's. 27th January, 1937. Mr. G. Jeger. The Spanish Medical Aid Committee, 24, New Oxford Street, W.C.1. Dear Mr. Jeger, GRANT. Referring to your letter of the 20th instant asking us to forward 500 in connection with the allotment made to your Committee as set out in my letter of 11th November, the matter is receiving consideration and I will write to you again as soon as possible. Yours sincerely, General Secretary. 292/946/41/66